On the way to climate neutrality: Scenarios can facilitate the transition of companies and the financial sector - Fernanda Ballesteros; Alexandra Hüttel; Karsten Neuhoff; Catherine Marchewitz (DIW Weekly Report, 2023)
In its Federal Climate Change Act, Germany has committed to achieving climate neutrality by 2045. To do so, companies from both the industrial and the service sectors must adjust their production and business practices, and financial institutions must adjust their evaluation criteria. In many cases, this requires a new strategic direction and investments in climate-neutral products, business models, and production technology. To achieve this, companies require capital and support from the financial sector, which thusly plays a key role in achieving climate targets. For investors, civil society organizations, and government agencies to understand the investment needs, progress, and potential risks of companies as they transition to climate neutrality, companies are expected to provide forward-looking climate-related reporting based on scientific evidence and standardized procedures. Science utilizes scenarios, which can provide industrial and service companies as well as banks, funds, and insurance companies with standardized and comparable information about the transition to a climate-neutral business model and the resulting risks. Scenarios allow companies in the real economy to systematically consider transition risks and opportunities when making decisions about investments and strategic direction. Furthermore, the scenarios make it possible for the financial industry to gradually decarbonize its investment portfolio and to depict company-specific transition risks and opportunities in risk management.
Keywords: E61; E44; Q54; Q56; Q58; 330; Scenario analysis; net zero; transition plans; forward-looking reporting; transition risks